Diverse Trajectories Drive the Expression of a Giant Virus in the Oomycete Plant Pathogen Phytophthora parasitica - Hannat, Sihem; Pontarotti, Pierre; Colson, Philippe; Kuhn, Marie-Line; Galiana, Eric; La Scola, Bernard; Aherfi, Sarah; Panabières, Franck (Frontiers in Microbiology, 2021)
Giant viruses of amoebas, recently classified in the class Megaviricetes, are a group of viruses that can infect major eukaryotic lineages. We previously identified a set of giant virus sequences in the genome of Phytophthora parasitica, an oomycete and a devastating major plant pathogen. How viral insertions shape the structure and evolution of the invaded genomes is unclear, but it is known that the unprecedented functional potential of giant viruses is the result of an intense genetic interplay with their hosts. We previously identified a set of giant virus sequences in the genome of P. parasitica, an oomycete and a devastating major plant pathogen. Here, we show that viral pieces are found in a 550-kb locus and are organized in three main clusters. Viral sequences, namely RNA polymerases I and II and a major capsid protein, were identified, along with orphan sequences, as a hallmark of giant viruses insertions. Mining of public databases and phylogenetic reconstructions suggest an ancient association of oomycetes and giant viruses of amoeba, including faustoviruses, African swine fever virus (ASFV) and pandoraviruses, and that a single viral insertion occurred early in the evolutionary history of oomycetes prior to the Phytophthora–Pythium radiation, estimated at ∼80 million years ago. Functional annotation reveals that the viral insertions are located in a gene sparse region of the Phytophthora genome, characterized by a plethora of transposable elements (TEs), effectors and other genes potentially involved in virulence. Transcription of viral genes was investigated through analysis of RNA-Seq data and qPCR experiments. We show that most viral genes are not expressed, and that a variety of mechanisms, including deletions, TEs insertions and RNA interference may contribute to transcriptional repression. However, a gene coding a truncated copy of RNA polymerase II along a set of neighboring sequences have been shown to be expressed in a wide range of physiological conditions, including responses to stress. These results, which describe for the first time the endogenization of a giant virus in an oomycete, contribute to challenge our view of Phytophthora evolution.